2017
DOI: 10.3174/ajnr.a5424
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of Quantitative Dynamic Postgadolinium MRI Technique Using Normalized Ratios for the Evaluation of Temporomandibular Joint Synovitis in Patients with Juvenile Idiopathic Arthritis

Abstract: We provide a robust, reproducible, dynamic gadolinium-enhanced MR imaging technique for the quantitative assessment of temporomandibular joint synovitis in patients with juvenile idiopathic arthritis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 7 publications
1
2
0
Order By: Relevance
“…Likewise, Ma et al [ 38 ] compared a metric that evaluated only the change in SI pre- versus post-administration of gadolinium with a metric that measured a signal to noise ratio based upon enhancement in surrounding tissue, studying 67 children with JIA and 24 non-arthritic controls. Consistent with the study by Caruso et al [ 37 ], Ma et al concluded that the ER, which incorporated the extent of enhancement in the surrounding tissue, was better able to discriminate JIA patients with mild disease from controls [ 38 ]. While the optimal method of assessing the extent of TMJ joint fluid or enhancement in controls may not be entirely clear, it is evident that small amounts of joint fluid and CE in non-arthritic subjects are common.…”
Section: Methodssupporting
confidence: 70%
See 1 more Smart Citation
“…Likewise, Ma et al [ 38 ] compared a metric that evaluated only the change in SI pre- versus post-administration of gadolinium with a metric that measured a signal to noise ratio based upon enhancement in surrounding tissue, studying 67 children with JIA and 24 non-arthritic controls. Consistent with the study by Caruso et al [ 37 ], Ma et al concluded that the ER, which incorporated the extent of enhancement in the surrounding tissue, was better able to discriminate JIA patients with mild disease from controls [ 38 ]. While the optimal method of assessing the extent of TMJ joint fluid or enhancement in controls may not be entirely clear, it is evident that small amounts of joint fluid and CE in non-arthritic subjects are common.…”
Section: Methodssupporting
confidence: 70%
“…These ratios were (postGadolinium SI in the TMJ – preGadolinium SI in the TMJ)/(postGadolinium SI in the longus capitus – preGadolinium SI in the longus capitus); (postGadolinium SI in the TMJ – preGadolinium SI in the TMJ)/(postGadolinium of longus capitus); and (postGadolinium SI of TMJ)/(postGadolinium SI of longus capitus). Of those three, they concluded that the most favorable measure was the second (postGadolinium SI in the TMJ – preGadolinium SI in the TMJ)/(postGadolinium of longus capitus), due to optimal discrimination among the three groups and a lack of a substantial increase over time [ 37 ]. Likewise, Ma et al [ 38 ] compared a metric that evaluated only the change in SI pre- versus post-administration of gadolinium with a metric that measured a signal to noise ratio based upon enhancement in surrounding tissue, studying 67 children with JIA and 24 non-arthritic controls.…”
Section: Methodsmentioning
confidence: 99%
“…Changes in the TMJ score between repeat imaging of the same state of disease may be significant when the imaging parameters are not standardized, or the imaging interval is long enough to introduce physiological changes. Quantitative methods for scoring the degree of inflammation have demonstrated a high degree of discriminatory validity [ 26 , 27 ] but are also affected by temporal variations [ 28 ]. In a semiquantitative scoring system such as the JAMRIS-TMJ, these errors may be relatively low compared to the between-reader variance but should still be accounted for when using the scoring system in longitudinal evaluation.…”
Section: Discussionmentioning
confidence: 99%